Mancha-foliar-de-Phyllosticta em gengibre. caracterização cultural do patógeno e efeito de tratamentos químicos no controle da doença em Morretes, Estado do Paraná - Cerezine, P. C.; Olinisky, I. A.; Bittencourt, MVL; Valerio, W. V. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
The objectives of this work were to determine the micelial growth curve of the pathogen and the sensitivity to some fungicides potencially efficient to disease control. The optimum temperature range for micelial growth of Phyllosticta sp, was between 25 and 27.5 degrees C. The maximum and minimum temperatures for micelial growth were 32.5 degrees C and 10 degrees C. Temperatures of 5 and 35 degrees C completely inhibited the growth of the isolates. Total inhibition of the micelial growth was observed with captan and mancozeb (1000 mg a.i./ml) and triadimenol (100 mg a.i./ml). Partial reduction of the micelial growth was observed with iprodione, methyl tiofanate and chlorothalonil until 1.000 mg/ml. The chemical control of PLS was studied in a commercial area of ginger ''Gigante'', in Morretes, PR, where 18 sprays were carried out, with a break of 7 to 10 days, from December to April. The highest reduction of the area under the disease progress curve standardized (AUDPCs) was observed with the spray of chlorothalonil. With the application of dithianon, cupper oxychloride, folpet, mancozeb and captan it was observed AUDPCs between 15.05 and 18.61 lesions/leaf. Iprodione, benomyl, triadimenol and methyl tiofanate did not control the disease (AUDPCs between 20.03 and 25.04 lesions/leaf). The AUDPCs in the check plot was 35.88 lesions/leaf. There was no significant difference of vigor and of ginger yield between fungicide treatments. The cupper oxichloride was phytotoxic to ginger.

Os objetivos deste trabalho foram determinar o crescimento da curva micelial do patógeno e a sensibilidade a alguns fungicidas potencialmente eficientes no controle da doença. A faixa ótima para crescimento micelial dos isolados de Phyllosticta sp., in vitro, situou-se entre 25 a 27,5 °C. As temperaturas máximas a mínimas para o crescimento do patógeno foram 32,5 a 10 ºC. Inibição total do crescimento micelial foi constatada também com captan a mancozeb a 1.000 mg i.a./ml e triadimenol a 100 mg i.a./ml. Redução parcial do crescimento micelial foi observada com iprodione, tiofanato metílico e chlorothalonil 1.000 mg/ml. Quanto ao controle químico da mancha-foliar-de-Phyllosticta em gengibre "Gigante", este foi estudado em Morretes, PR, na safra de 1991/92. Foram efetuadas 18 pulverizações, em intervalos de 7 a 10 dias, entre dezembro e abril. Chlorothalonil proporcionou a maior redução da área sob a curva de progresso de doença estandardizada (ASCPDe). Com relação a dithianon, oxicloreto de cobre, folpet, mancozeb e captan, constatou-se ASCPDe entre 15,05 a 18,61 lesões/folha doente. Já iprodione benomyl, triadimenol e tiofanato metílico não controlaram a doença. A ASCPDe da testemunha foi de 35,88 lesões/folha doente. Não houve diferença entre tratamentos com relação ao vigor das plantas de gengibre e à produção. O fungicida oxicloreto de cobre foi fitotóxico ao gengibre.
Phyllosticta leaf-spot on ginger cultural characterization of the pathogen and effect of chemical treatments on disease-control in Morretes, Parana state, Brazil
Keywords: ZINGIBER OFFICINALE; PHYLLOSTICTA SP; CHEMICAL CONTROL